2000
DOI: 10.1007/s001250051366
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides, apo C3 and Lp B:C3 and cardiovascular risk in Type II diabetes

Abstract: Cardiovascular disease is a major cause of morbidity and mortality in Type II (non-insulin-dependent) diabetes mellitus. Most of the patients die from cardiovascular complications, particularly from ischaemic heart disease [1±3].The mechanisms responsible for the increased cardiovascular risk in Type II diabetes are not fully understood. Diabetes is associated with many well-established cardiovascular risk factors. Patients with Type II diabetes have characteristic lipid abnormalities related to insulin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 30 publications
4
55
0
3
Order By: Relevance
“…Likewise only a few small studies have reported apo CIII levels in a diabetic population and the data are inconclusive [14][15][16][17]. In the context of CHD risk, current evidence suggests that the increase of apolipoprotein CIII in TRLs may be an independent risk factor for coronary heart disease [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise only a few small studies have reported apo CIII levels in a diabetic population and the data are inconclusive [14][15][16][17]. In the context of CHD risk, current evidence suggests that the increase of apolipoprotein CIII in TRLs may be an independent risk factor for coronary heart disease [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…We prioritised biomarkers of cardiac damage (highsensitivity troponin T [hsTnT] and N-terminal pro-B-type natriuretic peptide [NT-proBNP]), renal disease (cystatin C, fetuin A), glucose-mediated damage in diabetes (soluble receptor for AGE [sRAGE]), matrix remodelling (matrix metalloproteinases and osteopontin) and coagulation (factor VII), as well as a lipoprotein of particular interest in diabetes (apolipoprotein C-III [apoCIII]) [9,10], and a large set of immune-and inflammation-related proteins including interleukins and interferons. We measured 33 protein biomarkers (ESM Table 2) by multiplex immunoassay on the Human DiscoveryMAP customised panel using the Luminex 100/200 instrument by RBM (Myriad Rules Based Medicine, Austin, TX, USA) [11] and standard commercially available ELISAs and kits for nine biomarkers.…”
mentioning
confidence: 99%
“…A number of clinical studies have revealed that total apoC-III as well as apoC-III present on TRLs (LpB:C-III) are risk indicators for CVD (23,24). In the Monitored Atherosclerosis Regression Study (MARS) (25), apoC-III, particularly in apoB-containing lipoproteins, was a major risk factor for the severity of CVD in patients with mild and moderate atherosclerosis.…”
mentioning
confidence: 99%